Effects of Fuel Penetration on the RDE Performance with JISC Injector Configuration - Gyeong-Ui Mo; In-Hoi Koo; Keon-Hyeong Lee; Su-Wan Choi; Jeong-Yeol Choi (Aerospace)
This study investigates the operational characteristics of the Rotating Detonation Engine (RDE), with a focus on fuel injector design. Inspired by the similarity between the fuel injection structure of RDE and the Jet in Supersonic Crossflow (JISC) of a scramjet, experimental research on fuel injectors with jet penetration was conducted. Five injectors were designed, each with a fixed fuel injection area or injection hole diameter. Experiments determined practical injection areas, and an empirical correlation was used to calculate jet penetration heights. Under conditions of a total mass flow rate of 105 ± 5 g/s and an equivalence ratio of 1.05 ± 0.1, combustion modes were analyzed. Initial detonation occurrence was assessed through pressure history, with a detailed analysis via image post-processing. The results indicated that the injector D4N15, with the highest jet penetration height, exhibited deflagration, while D4N23 showed chaotic propagation. The injector D2N60 demonstrated relatively unstable behavior in sustained detonation cases. Thrust comparisons revealed that D4N30, with wider hole spacing and higher jet penetration height, exhibited approximately 12.5% higher specific impulse compared to D1N240. These outcomes confirm the significant impact of jet penetration height and hole spacing on detonation propagation and engine performance.